Analysis of Acceleration of Completion of Palapa Market Revitalization Project Using Crash Program Method - Puspita Sari, Neri; Yasri, Desi; Ovirizalni, Nurul (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2025)
Timeliness in construction projects is a crucial factor that affects cost, quality, and stakeholder satisfaction. Delays in project completion can have serious consequences. The Palapa Market Revitalization Project in Pekanbaru City with a contract value of Rp2,791,647,140.00 and a planned duration of 120 calendar days experienced a delay of -7.42% in the 13th week. This problem prompted this study to analyze project scheduling using the Precedence Diagram Method (PDM) to identify critical path activities and accelerate them through the Crash Program method by adding overtime work for 1, 2, 3, and 4 hours. The results of the study indicate that critical activities that can be accelerated include Steel Column Work, Steel Beam Work, and Hollow Frame Painting Work. The optimal acceleration scenario is the addition of overtime for 1 hour per day, so that the duration of the Steel Column Work is reduced to 125 days from 129 days at a cost of Rp. 215,719,694.80 (from Rp. 190,999,200.00), Steel Beam Work reduced to 125 days from 129 days at a cost of Rp. 80,595,986.13 (from Rp. 72,212,000.00), and Hollow Frame Painting Work reduced to 126 days from 129 days at a cost of Rp. 17,591,213.87 (from Rp. 15,635,200.00). These results indicate the effectiveness of the schedule acceleration strategy in mitigating project delays by considering cost implications.